Asphalt-Rubber SAMI (Stress-Absorbing Membrane Interlayers) Field Evaluation. - McKeen,R G; Pavlovich,Raymond D; Cassino,Vincent (1986)
This report documents the investigation of asphalt-rubber mixtures for use as stress-absorbing membrane interlayers (SAMIs) for airfield pavements. The project was initiated in 1977 as a state-of-the-art review (Reference 1). That study concluded that use of SAMIs was promising for improving the performance of asphalt-concrete overlays on airfield pavements. A following study addressed material characterization and development of a proposed construction specification (Reference 2). This report covers follow-on monitoring of the performance of an experimental pavement project at Kirtland AFB, Apron A; construction and performance monitoring of two trial sections located at Williams AFB and Coolidge Field in Arizona; and the design and construction of a field experiment at Peterson AFB, Colorado. Based on the results obtained to date, the performance observed cannot be related in a meaningful way to the material characteristics. This results from the small time elapsed since construction of the pavements under observation. Based on experience, a revised proposed construction specification is included in the current report. Continued performance monitoring is recommended in order to obtain the benefit from the investment made in the initial construction documentation. Keywords: Airfield parameters, Asphalt rubber, Performance monitoring, Field observations, Reflection cracking.